Urban Live Stock Farm - MUHAMED YOGA DWIAJIWIYARNO (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2026)
UrbanLivestockFarmis a sustainable urban farming facility that integrates livestock production, food processing, education, and public spaces within a modern architectural environment. The project promotes food security, environmental responsibility, and community engagement through innovative farming technologies and circular resource management systems.